2022
DOI: 10.3390/genes13030515
|View full text |Cite
|
Sign up to set email alerts
|

High Resistance to Quinclorac in Multiple-Resistant Echinochloa colona Associated with Elevated Stress Tolerance Gene Expression and Enriched Xenobiotic Detoxification Pathway

Abstract: Echinochloa colona and other species in this genus are a threat to global rice production and food security. Quinclorac, an auxin mimic, is a common herbicide for grass weed control in rice, and Echinochloa spp. have evolved resistance to it. The complete mode of quinclorac action and subsequent evolution of resistance is not fully understood. We analyzed the de novo transcriptome of multiple-herbicide-resistant (ECO-R) and herbicide-susceptible genotypes in response to quinclorac. Several biological processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Among grasses, Echinochloa ssp. is reported in two articles [ 9 , 14 ] and L. multiflorum in one [ 8 ]; among dicots, two articles reported on the global invasive weed species A. palmeri [ 10 , 13 ]. All these weeds are acknowledged to be among the top 10 weed species resistant to most SoAs globally [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among grasses, Echinochloa ssp. is reported in two articles [ 9 , 14 ] and L. multiflorum in one [ 8 ]; among dicots, two articles reported on the global invasive weed species A. palmeri [ 10 , 13 ]. All these weeds are acknowledged to be among the top 10 weed species resistant to most SoAs globally [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, information on the resistance to auxins in Echinochloa ssp. [ 14 ], microtubule assembly [ 13 ], and PPO inhibitors [ 10 ], both in A. palmeri , are contributions of this Special Issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some PSCS and CDPK genes were involved in the regulation of proline biosynthesis and the translation of phosphorylation signals, respectively, and both played a role in responding to abiotic stress in plants ( Franz et al, 2011 ; Asano et al, 2012 ). Recent studies have shown that herbicides stress could induce changes in the transcription levels of P5CS and CDPK genes in plants ( Boulahia et al, 2016 ; Wang et al, 2021 ; Rangani et al, 2022 ). It was reported that P5CS activity and its gene expression level were reduced by exogenous application of ethanolamine ( Rajaeian et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%